REGULATORY APPROACHES OF THE RIGHT TO INFORMATION ACCESS IN THE ARAB STATES (Law, State and Telecommunications Review, 2021)
Purpose – However, the Right to Access to Information (RTI)[1] is guaranteed by article 91 of the Universal Declaration of Human Rights and more than 120 have adopted such a right, fewer Arab countries; mainly in Tunisia, Egypt, Morocco and Algeria, whose constitutions included the right of people to access information. Hence, the purpose of this research is to assess and provide an in-depth study of the status quo of the right to access to public information in the Arab region as well as to highlight whether the adopted laws have met people need of information.Methodology/Approach/Design – In order to achieve the purpose of this research project, a ‘non-doctrinal’ empirical socio-legal research type of qualitative method has been undertaken to examine the right to access and request information in Arab States.Findings – The paper findings shows that Arab countries are not keeping the pace on adopting and implementing the Right to Access to Information laws where culture of secrecy prevails and overcomes the openness in the Arab World. 1 The term “Right to Access to Information” RTI will be used in this article interchangeably as the right to information RTI, Freedom of Information FOI, and Right to Know RTK. Calland 2010 refers to the terminology point by stating that civil society activists, advocates and authors do not prefer using the ‘Freedom of Information’ terminology of choice in this field; instead, ‘the right of access to information’ (ATI) or ‘the right to know’ RTK have gained a kind of ascendency in the past years.